Impact of Anticipated Awake Surgery on Psychooncological Distress in Brain Tumor Patients - Staub-Bartelt, Franziska; Radtke, Oliver; Hänggi, Daniel; Sabel, Michael; Rapp, Marion (Frontiers in Oncology, 2022)
BACKGROUND Brain tumor patients present high rates of distress, anxiety, and depression in particular perioperatively. For resection of eloquent located cerebral lesions awake surgery is the gold standard surgical method for preservation of speech and motor function which might be accompanied by increased psychological distress. Aim of the present study was to analyse if patients planned for awake craniotomy suffer from increased prevalence or higher scores in distress, anxiety or depression. METHODS Patients, who were elective admitted for brain tumor surgery at our neurooncological department, were perioperatively screened regarding distress, anxiety and quality of life using three established self-assessment instruments (Hospital Anxiety and Depression Scale, Distress Thermometer, EORTC-QLQ-C30-BN20). Screening results were compared concerning operation technique (awake vs. asleep). Retrospective statistical analyses for nominal variables were conducted using Chi-square-test. Metric variables were analysed using the Kruskal-Wallis-Test, the Man-Whitney-U-Test and Independent-sample T-tests. . RESULTS Data from 54 patients (26 male, 28 female) aged 29 to 82 years were available for statistical analyses. 37 of the patients received primary and 17 recurrent tumour resection. Awake surgery was planned for 35 patients. There was no significant difference in awake versus non awake surgery patients regarding prevalence (of distress (p=.695), anxiety (p=.165) or depression (p=.786). Furthermore, awake surgery had no significant influence on distress thermometer score (p=.470), anxiety-score (p=.461) or depression-score (p=.417) as well as future uncertainty (p=.436) or global health-status (p=.943). Additionally, analyses revealed that primary or recurrent surgery also did not have any significant influence on prevalence or scoring of the evaluated items. CONCLUSION Analyses of our cohort’s data suggest that planned awake surgery might not have a negative impact on patients concerning the prevalence and severity of manifestation of distress, anxiety or depression in psychooncological screening. Patients undergoing recurrent surgery tend to demonstrate increased distress-although results were also not significantly.